Root length density in maize (Zea mays L.) intercropped with cowpeas (Vigna uguiculata L.) within the same basin or outside the basin in a semi-arid area of Zimbabwe - Dube, E.D.N; Madanzi, Tendai; Kapenzi, Arnold; Masvaya, E. (Scientific Research Publishing, 2016)
A study to assess the effect of intercropping maize (Zea mays L.) and cowpea (Vigna unguiculata L.) within the same basin or outside the basin on root length density (RLD) was conducted at the International Crop Research Institute for Semi-Arid Tropics (ICRISAT) Matopos Research Station from December 2009 to April 2010. The experiment was laid out in a Randomised Complete Block Design (RCBD) with four treatments replicated four times namely; sole maize, sole cowpea, maizecowpea intercrop with cowpea and maize planted within the same basin and maize-cowpea intercrop with cowpea planted 20 cm outside the maize basin. There was significant difference (P < 0.001) in RLD, grain yield and stover yield. Maize-cowpea intercropped within the same basin achieved higher RLD, grain yield and stover yield than cowpea that was intercropped outside the basin and the sole crops. The land equivalent ratio (LER) in both intercrop designs showed that intercropping had better grain yield performance when compared to sole cropping. It can be concluded that intercropping maize and cowpeas within the same basin can result in an environment around the crop achieving higher RLD which translates to better grain yield compared to the sole cropping and intercropping cowpeas outside the basin.